Berberine promotes immunological outcomes and decreases neuroinflammation in the experimental model of multiple sclerosis through the expansion of Treg and Th2 cells - Maryam J. Tavaf; Azita Soltanmohammadi; Simin Zargarani; Esmaeil Yazdanpanah; Bizhan Sadighimoghaddam; Bahman Yousefi; Hamid R. Sameni; Dariush Haghmorad (Immunity, Inflammation and Disease)
Abstract Introduction Among the most frequent demyelinating autoimmune disorders of the central nervous system (CNS) is multiple sclerosis. Experimental autoimmune encephalomyelitis (EAE) is used as an animal model of multiple sclerosis. Berberine is an alkaloid found in some medicinal plants with anti‐inflammatory effects. Methods C57BL/6 female mice were used and divided into three groups: (1) The control group received PBS, (2) the low‐dose treatment group received 10 mg/kg of berberine, and (3) The high‐dose treatment group received 30 mg/kg of berberine. Myelin Oligodendrocyte Glycoprotein and complete Freund's adjuvant were subcutaneously administered to induce EAE. Mice were given intraperitoneal injections of pertussis toxin on the day of immunization and 2 days later. Histological studies showed low lymphocyte infiltration and demyelination of CNS in the treated groups. Results The clinical scores of the treatment group with low‐dose berberine (T1: 2 ± 0.13) and high‐dose berberine (T2: 1.5 ± 0.14) were significantly (p < .001) lower than the control group (CTRL: 4.5 ± 0.13). Treatment groups decreased pro‐inflammatory cytokines (IFN‐γ, TNF‐α, interleukin [IL]‐17) (p < .001) as well as increased anti‐inflammatory cytokine expression (IL‐4, IL‐10, IL‐27, IL‐33, IL‐35, TGF‐β) (p < .01) when compared to the CTRL group. Treatment groups with berberine reduced expression of the Th1 and Th17 cytokines and transcription factors (p < .001) and increased expression of transcription factors and Th2 and Treg cytokines (p < .01) in contrast to CTRL group. Conclusion Berberine appears to have a protective effect on disease development and alleviating disease status in EAE, which appears to be due to the cell expansion and function of Treg and Th2 cells in addition to berberine's anti‐inflammatory properties.